Pathogenetic features of morphodensitometric characteristics of cardiomyocytes and marker profile of the left ventricular remodeling in rats with experimental intermittent hypoxia of different duration - Yu. M. Kolesnyk; M. I. Isachenko (Kazimierz Wielki University, 2020)
Myocardial remodeling is considered as a three-component complex process, including cardiomyocyte hypertrophy, their apoptosis, interstitial and perivascular fibrosis. At the same time, the nature of remodeling and the direction of restructuring in the myocardium depend on the prevalence of one of these processes, the degree of their severity and the impact duration. Therefore, to understand the effect of short- and long-term intermittent hypoxia on the direction of myocardial remodeling and its type, the aim of this study was to determine the pathogenetic features of the morphodensitometric characteristics of cardiomyocytes and the marker profile of left ventricular myocardial remodeling in the rats with experimental intermittent hypoxia durated 15 and 60 days. Material and methods. A total of 30 male Wistar rats aging 6-10 months were used for the experiment and assigned to 3 experimental groups of 10 animals each: control; rats exposed to 15-day hypoxia; rats exposed to 60-day hypoxia. The object of the study was the left ventricular myocardium. The number of nuclei in an image, their average linear size and density (the ratio of the total area of nuclei to the area of the cytoplasm), and the concentration of RNA in the nucleus and cytoplasm were measured in the sections stained by Einarson via morphodensitometric method. An immunofluorescence method was used to study the content of immunoreactive material to markers of remodeling (cardiotrophin-1, type I collagen, titin, annexin V). As a result of the study, it was found that intermittent hypoxia led to a decrease in the number of nuclei in cardiomyocytes in both experimental groups compared to the control. Such changes in the number of nuclei were accompanied by significantly larger nuclear size compared to the control (in rats with 15-day hypoxia by 52.9 %, in rats with 60-day hypoxia - by 153.4 %) and a decrease in the density of nuclei in relation to the cytoplasm by 19.5 % and 21.2 %, respectively. In both groups, a significantly lower control concentration of RNA in the nuclei of cardiomyocytes was found alongside with an increase in their area. Such changes were accompanied by a significantly higher concentration of RNA by 23.2 % in the cytoplasm in case of long-term intermittent hypoxia. The marker profile of remodeling parameters in rats exposed to 15-day hypoxia was characterized by a higher content of cardiotrophin-1 and titin by 11.5 % and 23.1 %, respectively, as compared to the control. The content of type I collagen was 19.9 % higher, while the content of annexin V did not change significantly. In rats with long-term 60-day hypoxia, the content of cardiotrophin-1 was higher by 73.6 %, titin - by 124.9 %, type I collagen - by 41.9 %, and annexin V - by 95.9 % in comparison to the control. When calculating the titin / collagen ratio in rats based on their content, a significant increase in myocardial stiffness was determined in the 60-day hypoxia group which was 1.44, while it was0.91 in the control, and in rats with 15-day short-term hypoxia - 0.93. Conclusions. Intermittent hypoxic effects, regardless of duration, result in morpho-structural rearrangements of the myocardium, are characterized by an increase in viscoelastic mechanical properties and the development of hypertrophy, but with an increase in the duration of exposure (60 days) - by an additional formation of interstitial fibrosis and apoptosis of cardiomyocytes. Short-term hypoxia forms a hypertrophic type of myocardial remodeling with a decrease in the number of nuclei alongside with an increase in their size and a moderate decrease in RNA concentration. The marker profile of remodeling changes in a physiological manner and is characterized by an increase in the content of cardiotrophin-1, type I collagen and titin, while maintaining the titin / collagen ratio and normal apoptotic rate. Long-term hypoxia causes a fibro-apoptotic type of pathological myocardial remodeling including an almost two-fold decrease in the number of nuclei with an increase in their size and a decrease in RNA concentration. The marker profile of remodeling is characterized by an increase in all 4 components, a significant increase in the titin / collagen ratio and high apoptotic rate of cardiomyocytes.